Dealers' satisfaction with service quality of pre delivery inspection at Honda Malaysia Sdn Bhd / Afeira Helena Zainudin - Zainudin, Afeira Helena (Faculty of Business and Management, 2008)
Pre Delivery Inspection (PDI) is of the sections at Honda Malaysia Sdn Bhd. Honda has been a strong and aggressive player in the Malaysian automotive market. All cars must be thoroughly inspected at PDI before being delivered to dealers. There are 3 units in PDI which are accessorized and budget, quality and logistic, and operation. This section's function is to deliver quality car to dealers. There are 5 steps before the cars are released from PDI. This process includes receiving, accessorizing; inspection, washing and leak testing and loading. The main purpose of this study is to identify the current level of service quality given by Pre Delivery Inspection (PDI) of HMSB to the dealers, to know which of the 5 dimensions of service quality (tangibles, reliability responsiveness, assurance and empathy) that is the most influence of dealers satisfaction towards services quality provided by PDI of HMSB, to examine the significant relationships between dealer's satisfaction with the 5 dimensions (tangibles, reliability, responsiveness, assurance and empathy) and to give the recommendations for PDI HMSB in order to satisfy the dealers' expectations of the service quality. This research is conducted by using non-probability sampling and the sampling method is convenience sampling. The sampling size would be 50 respondents however only 39 have been answered. It has been taken conveniently at KAH Motor Melaka. From the finding the most influence of dealers' satisfaction towards services quality is assurance. As a conclusion on this research all objectives have successfully been met. Based on the finding, some recommendations have been suggested in order to enhance the dealers' satisfaction.